Phase II Study of ENZAlutamide Combined With Hypofractionated Radiation Therapy (ENZART) for Localized Intermediate Risk Prostate Cancer - Lara, Pedro C.; Rodríguez-Melcón, Juan I.; Palacios-Eito, Amalia; Lozano, Antonio; Hervás-Morón, Asunción; Villafranca, Elena; Gómez-Iturriaga, Alfonso; Sancho, Gemma; Maldonado, Xavier (Frontiers in Oncology, 2022)
Background Intermediate-risk prostate cancer (PCa) is usually treated by a combination of external beam radiation therapy (EBRT) and a short course of androgen deprivation therapy (ADT). ADT is associated with multiple side effects, including weight gain, loss of libido, and hot flashes. In contrast, anti-androgen monotherapy is generally better tolerated in spite of higher rates of gynecomastia. Objective This study assessed the effectiveness of enzalutamide monotherapy combined with hypofractionated EBRT (Hypo-EBRT) for treating intermediate risk prostate cancer. Method This trial was a multicenter, open-label phase II study of 6 months of enzalutamide monotherapy combined with Hypo-EBRT for intermediate-risk prostate cancer. Hypo-EBRT was initiated 8–12 weeks after initiating enzalutamide. The primary endpoint was PSA decline >80% measured at the 25th week of enzalutamide administration. Secondary end-points included assessment of toxicity, changes in anthropomorphic body measurements, sexual hormones, and metabolic changes. Results Sixty-two patients were included in the study from January 2018 to February 2020. A PSA decline of >80% was observed in all evaluable patients at the end of enzalutamide treatment and 92% achieved PSA values under 0.1 ngr/ml. All patients remain in PSA response (<80% reduction of the initial values) 6 months after the end of enzalutamide treatment. The most frequent adverse events were hypertension, asthenia, and gynecomastia. There were no significant changes in bone density, body mass index (BMI), or patient-reported outcomes (PROs). Conclusion Enzalutamide monotherapy is very effective along with hEBRT in reducing PSA levels for patients with intermediate-risk prostate cancer. Longer follow-up is needed to confirm the potential use of this combination in future randomized trials.